Strategy I responses to Fe-deficiency of two Citrus rootstocks differing in their tolerance to iron chlorosis - Martínez-Cuenca, Mary-Rus; Forner-Giner, María A.; Iglesias, Domingo J.; Primo-Millo, Eduardo; Legaz, Francisco (2017)
The expression of iron (Fe) acquisition-related genes in roots was studied in roots of two different citrus seedlings, namely, Carrizo citrange (CC, Fe chlorosis-sensitive) and Cleopatra mandarin (CM, Fe chlorosis-tolerant), growing either with (control) or without (-Fe) Fe in the nutrient solution. Fe-deficiency increased expression of the gene HA] coding for proton-ATPase (H+-ATPase) enzyme in both genotypes, although no differences were observed between treatments among rootstocks. Furthermore, while the gene expression levels of FRO2 - which encodes the Ferric Chelate Reductase (FC-R) enzyme-, increased under -Fe condition in both genotypes, CM always recorded the highest activity. CC showed the greatest induction of genes IRT1 and IRT2 encoding two iron transporters, however only IRT1 was significantly induced by Fe starvation. Analysis of the enzymatic activities (H+-ATPase and FC-R) regulated by the aforementioned genes confirmed these results. Thus, in agreement with the acidification pattern registered, H+-ATPase activities were higher in -Fe plants than in controls, although no significant differences were detected between each treatment among rootstocks. Fe starvation also induced FC-R activity; however, this was greater in CM than in CC roots. Interestingly, root Fe-57 uptake rates from Fe-57-EDDHA solutions were increased by Fe-deficiency, especially in the CM genotype, and CM accumulated a much larger Fe pool in the root apoplast than CC. Taken together, the main trait determining Fe-chlorosis tolerance among these genotypes is the ability to boost Fe3+ reduction in response to Fe-deficiency through enhanced FRO2 gene expression. Moreover, Fe chlorosis resistance in these plants could be related to the amount of Fe stored in the root apoplast. (C) 2013 Elsevier B.V. All rights reserved.